Empathy and Theory of Mind in Multiple Sclerosis: A Meta-Analysis - Lin, XiaoGuang; Zhang, XueLing; Liu, QinQin; Zhao, PanWen; Zhong, JianGuo; Pan, PingLei; Wang, GenDi; Yi, ZhongQuan (Frontiers in Psychiatry, 2021)
Multiple sclerosis (MS) is an immune-mediated demyelinating disease of the central nervous system. Studies have shown that MS disrupts several social cognitive abilities (including empathy and theory of mind [ToM]). Overall ToM deficits in MS are well documented, but how the specific ToM subcomponents and empathic capacity are affected remains unclear. For this meta-analysis, we searched PubMed, Web of Science, and Embase from inception to July 2020. Effect sizes were calculated using Hedges g with a random-effects model. Thirty-three studies were included. Relative to healthy controls (HCs), patients with MS were moderately impaired in overall empathy (g = -0.67), overall ToM (g = -0.74), cognitive ToM (g = -0.72), and the overlapping domains of cognitive empathy/affective ToM (g = -0.79); no group differences were identified for affective empathy (g = -0.19). Compared with HCs, patients with relapsing-remitting MS (RRMS) and progressive MS were impaired in overall empathy, overall ToM, cognitive ToM, and cognitive empathy/affective ToM, without significant RRMS–progressive MS differences in impairment degree. We conducted the first meta-analytic review investigating the empathy and ToM functioning patterns in patients with MS and examined the overlapping and distinct subcomponents of these constructs. The findings suggest differential impairment of the core aspects of social cognitive processing in patients with MS, which may importantly inform the development of structured social cognitive MS interventions.